The Prospects and Challenges of Economic Liberalization in Reducing Poverty and Inequality in Indonesia - Alfath Bagus Panuntun El Nur Indonesia (Journal of Social Development Studies, 2021)
This article discusses whether economic liberalisation policies have succeeded in alleviating poverty and inequality in Indonesia. In addition, this article aims to provide alternative policies to strengthen Indonesia’s bargaining position in international trade forums by shifting the extractive industry to knowledge-based industries and fixing the fragile social protection system when faced with COVID-19. This article is written descriptively and analytically based on various data, such as literature, planning documents, news reports, and other sources. Despite the prospect of economic liberalisation, the findings show Indonesia has three main problems: statistical data that does not reflect reality, overlapping regulations, and weak governance. This article offers several policy recommendations that need improvement based on the “Going for Growth” framework. Keywords: economic liberalisation, poverty alleviation, inequality, social protection, and going for growth Tulisan ini mendiskusikan apakah kebijakan liberalisasi ekonomi berhasil dalam pengentasan kemiskinan dan ketimpangan di Indonesia. Selain itu, tulisan ini bertujuan untuk memberikan alternatif kebijakan dalam rangka memperkuat posisi tawar Indonesia dalam forum perdagangan internasional dengan menggeser industri ekstraktif ke industri berbasis pengetahuan, sekaligus membenahi sistem perlindungan sosial yang rapuh ketika dihadapkan pada COVID-19. Tulisan ini ditulis secara deskriptif dan analitis berdasarkan dukungan dari berbagai data, seperti literatur, dokumen perencanaan, laporan berita, dan sumber lainnya. Meskipun terdapat prospek dari liberalisasi ekonomi, temuan menunjukkan bahwa Indonesia memiliki tiga masalah utama: data statistik yang tidak mencerminkan realitas, regulasi yang tumpang tindih, dan lemahnya tata kelola pemerintahan. Tulisan ini menawarkan beberapa rekomendasi kebijakan yang perlu ditingkatkan berdasarkan kerangka berpikir “Going for Growth”. Kata kunci: liberalisasi ekonomi, pengentasan kemiskinan, ketimpangan, perlindungan sosial dan going for growth